Worker Displacement and Occupation-Specific Human Capital. (August 2014) - Ormiston, Russell
Decades of research have consistently demonstrated the long-term earnings losses associated with job displacement. Despite the pervasiveness of this result, there has been limited research explaining why displaced workers lose so much value in the labor market. This study examines the effect of occupation-specific human capital in moderating postdisplacement earnings losses using occupational data from the U.S. Department of Labor and the 2004–2010 Displaced Worker Surveys. Developing two measures of cross-occupational comparability, the results suggest that greater transferability of human capital across occupations plays a significant role in determining postdisplacement earnings.